2011
DOI: 10.3390/rs3112529
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral Remote Sensing from Unmanned Aircraft: Image Processing Workflows and Applications for Rangeland Environments

Abstract: Using unmanned aircraft systems (UAS) as remote sensing platforms offers the unique ability for repeated deployment for acquisition of high temporal resolution data at very high spatial resolution. Multispectral remote sensing applications from UAS are reported in the literature less commonly than applications using visible bands, although light-weight multispectral sensors for UAS are being used increasingly. . In this paper, we describe challenges and solutions associated with efficient processing of multisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
210
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(221 citation statements)
references
References 35 publications
8
210
0
3
Order By: Relevance
“…For instance, lightweight hyperspectral sensors for UAS are now available from different vendors (e.g., SPECIM; HYSPEX; HeadWall; see Appendix A), offering more defined and discrete spectral responses compared to the modified RGB or multiband cameras. Multispectral cameras commonly employ multiple lenses, which introduce band-to-band offsets that need to be adequately corrected in order to avoid artefacts introduced into the combined multiband product [48,49]. Both multispectral and hyperspectral cameras require radiometric calibration and atmospheric corrections to convert the recorded digital numbers (DN) to surface reflectance values to enable reliable assessment of ground features, comparison of repeated measurements, and reliable determination of spectral indices [50].…”
Section: Sensorsmentioning
confidence: 99%
“…For instance, lightweight hyperspectral sensors for UAS are now available from different vendors (e.g., SPECIM; HYSPEX; HeadWall; see Appendix A), offering more defined and discrete spectral responses compared to the modified RGB or multiband cameras. Multispectral cameras commonly employ multiple lenses, which introduce band-to-band offsets that need to be adequately corrected in order to avoid artefacts introduced into the combined multiband product [48,49]. Both multispectral and hyperspectral cameras require radiometric calibration and atmospheric corrections to convert the recorded digital numbers (DN) to surface reflectance values to enable reliable assessment of ground features, comparison of repeated measurements, and reliable determination of spectral indices [50].…”
Section: Sensorsmentioning
confidence: 99%
“…Several UAV platforms have been used in environmental applications primarily focused on geographic surveying and high-resolution temporal and spatial imaging to complement LIDAR and satellite measurements [4,5]. However, there remains a significant technology gap in the development of high-performance, high-sensitivity trace gas sensors for the more common, less expensive, and smaller UAVs that have payloads on the order of 1 kg.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results showed that UAV technologies have great potential to acquire such products. Other studies of a less common use of UAVs on remote sensing are presented by Laliberte et al, 2011, Turner et al, 2012and Khan et al, 2012 This paper shows a study of an UAV system used to acquire aerial images to generate orthoimages of a rural area, containing a small town. The main phases of work were subdivided into Photogrammetric flight mission, control and check points surveying, aerial triangulation, Digital Terrain Model (DTM) and orthoimage generation.…”
Section: Introductionmentioning
confidence: 99%